AYURVEDIC MANAGEMENT OF DIABETIC OPHTHALMOPLEGIA: A CASE STUDY - Sushobhitha M; Venkatesh B.A. (International Journal of Applied Ayurved Research, 2020)
Diabetes mellitus (DM) is a widely prevalent non communicable disease in recent times. In India, 62 million people (12.1%) live with DM. DM has many complications like diabetic nephropathy, neuropathy, foot ulcer, retinopathy. Diabetic neuropathy occurs in ~50% of individuals with type 1 and type 2 DM of more than 10 years. Mononeuropathy (dysfunction of isolated cranial or peripheral nerves) is rare complication of DM and involvement of the third cranial nerve is most common. In Ayurveda DM is correlated to Prameha, which is Vata predominant stage. Diabetic ophthalmoplegia is understood as vatapradhana Prameha upadrava. Management of ophthalmoplegia must include Kapha-medohara, Vatahara, balya and Brihmana drugs. Here a clinically diagnosed case of Diabetic ophthalmoplegia ( 6th nerve palsy) is treated with Ayurvedic treatments i.e; Nasya (Errhine therapy) with Ksheerabala taila 101 avartita, Sthanika Abhyanga (local oil massage) with Ksheerabala taila, ksheera dhooma (fumigation with milk) and other internal medications like Brihat Vata Chintamani, Astavarga Kashaya, dhanwantaram kashaya and Ksheerabala capsule. Total duration of treatment was 15 days. There was complete reduction in diplopia, headache, numbness of face and in restricted movement, marked improvement was seen in visual acuity (VA).